2019
DOI: 10.3390/molecules24122229
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cold-Adapted and Salt-Tolerant RNase R from Antarctic Sea-Ice Bacterium Psychrobacter sp. ANT206

Abstract: A novel RNase R, psrnr, was cloned from the Antarctic bacterium Psychrobacter sp. ANT206 and expressed in Escherichia coli (E. coli). A bioinformatics analysis of the psrnr gene revealed that it contained an open reading frame of 2313 bp and encoded a protein (PsRNR) of 770 amino acids. Homology modeling indicated that PsRNR had reduced hydrogen bonds and salt bridges, which might be the main reason for the catalytic efficiency at low temperatures. A site directed mutation exhibited that His 667 in the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Cold-adapted enzymes are considered to have potential biotechnological and industrial applications that require activity at mild temperatures and rapid heat inactivation rates, such as that found in molecular biology, medical research, food/feed processing, pharmaceuticals, detergents and cosmetics [ 45 , 47 , 48 , 49 ]. With regard to Psychrobacter, cold-adapted enzymes, such as ribonucleases, proteases, esterases and lipases, have been found in some species of this genus [ 45 , 47 , 50 , 51 , 52 ]. Nevertheless, the production of compounds that interfere with quorum sensing (QS) in Psychrobacter strains has been the subject of a limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cold-adapted enzymes are considered to have potential biotechnological and industrial applications that require activity at mild temperatures and rapid heat inactivation rates, such as that found in molecular biology, medical research, food/feed processing, pharmaceuticals, detergents and cosmetics [ 45 , 47 , 48 , 49 ]. With regard to Psychrobacter, cold-adapted enzymes, such as ribonucleases, proteases, esterases and lipases, have been found in some species of this genus [ 45 , 47 , 50 , 51 , 52 ]. Nevertheless, the production of compounds that interfere with quorum sensing (QS) in Psychrobacter strains has been the subject of a limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the identi ed keystone bacteria may be resistant to salinity. In fact, some members of Moraxellaceae and Planococcaceae have been isolated from various hypersaline habitats [58][59][60][61].…”
Section: Moraxellaceae and Planococcaceae As The Keystone Taxamentioning
confidence: 99%
“…This nding is consistent with our result that Psychrobacter was enriched in January when low temperature condition existed. Besides, some strains of Psychrobacter have been isolated and/or detected in variety of hypersaline surroundings [59,[62][63][64]. Psychrobacter sp.…”
Section: Moraxellaceae and Planococcaceae As The Keystone Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…RNase R from the Antarctic bacterium Psychrobacter sp. ANT206 was also found to be thermally instable but showed efficient catalytic activity at 30°C, suggesting that it is also cold‐adapted (Wang et al ., 2019). Since the discovery of RNase R as a novel component of RNA degradosome machinery in P. syringae , its genetic and biochemical characterization has demonstrated that the RNase R‐mediated RNA metabolism is crucial for cold adaptation (Fig.…”
Section: Properties Of Rnase R and Its Behaviour During Low‐temperature Degradation Of Rnamentioning
confidence: 99%